Integrated Urban Solid Waste Management: Knowledge, Practices, and Implementation - ALFARAS, Riza Stephanie A. (Journal of Environmental Management and Tourism, 2023)
The current study sets out to ascertain the residents of Kabankalan City's degree of solid waste management knowledge, practices, and implementation. This further established the relationship between their knowledge, practices, and degree of solid waste management program implementation. The researcher-made questionnaire was used to assess solid waste management practices and program implementation, while a modified version of the questionnaire from the study by Trondillo, et al. (2018) was utilized to assess knowledge levels. For the study, 365 residents of Kabankalan City were chosen at random. The primary analysis employed in this inquiry was the Pearson r correlation. According to the findings, locals have a fundamental grasp of and a modest level of practice with solid waste management. The city's solid waste management program was only partially implemented. Last but not least, the amount of knowledge and implementation was substantially correlated with the residents' solid waste management practices.